2017
DOI: 10.7448/ias.20.1.21847
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the WHO 90% target: antiretroviral treatment efficacy in Poland is associated with baseline clinical patient characteristics

Abstract: Introduction: Modern combined antiretroviral therapies (cART) allow to effectively suppress HIV-1 viral load, with the 90% virologic success rate, meeting the WHO target in most clinical settings. The aim of this study was to analyse antiretroviral treatment efficacy in Poland and to identify variables associated with virologic suppression.Methods: Cross-sectional data on 5152 (56.92% of the countrywide treated at the time-point of analysis) patients on cART for more than six months with at least one HIV-RNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
2
9
0
2
Order By: Relevance
“…This aspect was not analysed in our study, but Wójcik et al [9] showed that patients with better compliance had better virological effect. The cross-sectional study of 5152 Polish HIV-infected patients (56.9% of the country-wide treated patients on ART) demonstrated that the antiretroviral treatment success defined as 'undetectable HIV (viral load < 50 copies/ml)' was achieved in over 90% of the subjects [15]. These findings may confirm the very high compliance rate (median 100%) declared by the patients in our study.…”
Section: Discussionsupporting
confidence: 84%
“…This aspect was not analysed in our study, but Wójcik et al [9] showed that patients with better compliance had better virological effect. The cross-sectional study of 5152 Polish HIV-infected patients (56.9% of the country-wide treated patients on ART) demonstrated that the antiretroviral treatment success defined as 'undetectable HIV (viral load < 50 copies/ml)' was achieved in over 90% of the subjects [15]. These findings may confirm the very high compliance rate (median 100%) declared by the patients in our study.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, it was confirmed by Prof. Parczewski and co-authors in observational study, that the proportion of treated patients who achieve HIV RNA suppression in Poland is over 90% (13). Outcome from this study are very promising for the Polish population.…”
Section: Time Lapse Between Detection Of Hiv Infection and Aids Diagnmentioning
confidence: 59%
“…Pomimo to, jak potwierdzają także wyniki badań projektu TAK, znaczny odsetek osób z rozpoznanym zakażeniem HIV nie jest objętych opieką specjalistyczną po rozpoznaniu zakażenia -37,9% (88/232) (11,12). Natomiast jak wskazują wieloośrodkowe badania prof. Parczewskiego i wsp., odsetek pacjentów leczonych, którzy osiągają supresję HIV RNA wynosi ponad 90% (13). Wyniki tych badań dla populacji Polski są więc bardzo obiecujące, dlatego niski poziom objęcia leczeniem osób zakażonych przekłada się na zwiększone ryzyko wystąpienia AIDS w tej grupie oraz kontynuację ryzyka dalszej transmisji wirusa (14).…”
Section: Time Lapse Between Detection Of Hiv Infection and Aids Diagnunclassified
“…However, in the last decade, the predominant transmission route has shifted to sexual transmission, and the rate of HIV diagnosis is increasing among men who have sex with men (MSM) . Currently available combination antiretroviral therapy (cART), accessible via the framework of the Polish National HIV treatment programme, has resulted in notable national treatment success rates, with > 90% of patients treated achieving undetectable HIV viral loads . This has been associated with improved prognosis and a decrease in mortality among HIV‐infected patients.…”
Section: Introductionmentioning
confidence: 99%